If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 4 + -1y = 3y + -3 + 9 Reorder the terms: 4 + 2y + -1y = 3y + -3 + 9 Combine like terms: 2y + -1y = 1y 4 + 1y = 3y + -3 + 9 Reorder the terms: 4 + 1y = -3 + 9 + 3y Combine like terms: -3 + 9 = 6 4 + 1y = 6 + 3y Solving 4 + 1y = 6 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 4 + 1y + -3y = 6 + 3y + -3y Combine like terms: 1y + -3y = -2y 4 + -2y = 6 + 3y + -3y Combine like terms: 3y + -3y = 0 4 + -2y = 6 + 0 4 + -2y = 6 Add '-4' to each side of the equation. 4 + -4 + -2y = 6 + -4 Combine like terms: 4 + -4 = 0 0 + -2y = 6 + -4 -2y = 6 + -4 Combine like terms: 6 + -4 = 2 -2y = 2 Divide each side by '-2'. y = -1 Simplifying y = -1
| 9x-8x^2=0 | | -7+6x+x^2=0 | | 8(x-2)-3(2x-4)=2(x+3) | | 0.8x=1 | | 1=3x-15 | | p=50-1 | | r/8+15=12 | | -5(7b+3)=27+7b | | (3+.25w)*2+2w=60 | | 2k+7=11 | | 6+3w-w=4+2w+2 | | -4=-5+n | | 3/2+3/4a=2x+8-5x | | 2-8b=-10+4b | | 5-5x^2=0 | | 3-|7-6n|=-26 | | -4y+9=6y+2 | | 3z+11=5 | | 1/4-2+3=m | | 2d/3=12 | | -4(8+7x)=-10-6x | | 4y+16=.33(10y-4) | | -27=r-13 | | x^4-16x^2+40x-25=0 | | 1.0y+0.1y+0.0y=111 | | -8+4x^2=0 | | f(x)=20x+11 | | 19+45y=25-3y | | 7(8x+5)=35+4x | | 14x+9y=55 | | 2(3X+1)=5X*14 | | 7-3x-7x^2=0 |